The role of Islamic bond (sukuk) in green and sustainable Islamic finance: its connotation on social prosperity by realizing ESG - Mohammad, Habibullah (2023)
Abstract: Islamic finance offers a different route to meet the large funding requirements for sustainable development projects and activities in poor nations because of its social and moral ethos and asset-backed nature. Islamic finance and Environmental Social and Governance (ESG) investing often share guiding principles, which makes them complementary as capital-raising and investment strategies. By adding a second layer of governance (Shari’ah) that guarantees the ring-fencing of issue profits and directs them toward projects that align with Shari’ah rules and ESG criteria, Islamic finance encourages sustainable development and is in line with those requirements. Promoting financial inclusion for individuals who might refrain from using the financial system due to ethical considerations or a lack of access, are two significant obstacles to escaping poverty. This study aims to demonstrate how it can draw in funds from sources now unexplored by traditional green and sustainable finance. Due to the fundamental principle of avoiding speculative and toxic financial products based on derivatives, generally full collateralization due to its asset-backed structure, and intimate ties to the actual economy, it can preserve sustainability and stability during financial crises. Proceeds from green, sustainability, and social bonds are meant to fund legitimate initiatives or assets that support particular goals. Even though these bonds are not always asset-backed or asset-based, the ESG bond framework creates a strong link between the capital raised and the issuer's underlying strategy and asset mix, which is consistent with the fundamentals of Islamic financing. In order to accomplish this goal, a systematic literature review methodology is used in this study to explore the fact that Green Sukuk (bonds) are currently being issued with the goal of funding environmentally friendly, climate-resilient, and sustainable growth. The market's organic growth, investors' growing interest in moral and ethical investing, the stringent capital requirements for infrastructure project financing, and the growing trend toward adopting green Sukuk (bonds) have all influenced this development.